2014
DOI: 10.1159/000365358
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of the Effect of Alcohol Intake on the Risk of Urolithiasis Including Dose-Response Relationship

et al.

Abstract: Objective: We conducted a meta-analysis to quantitatively evaluate the correlation between alcohol consumption and the risk of urolithiasis by summarizing the results of published case-control and cohort studies and the potential dose-response association. Methods: A systematic literature search of articles up to February 2014 was conducted via PubMed, Web of Science, Cochrane Library, Scopus, EMBASE, the Chinese National Knowledge Infrastructure databases, and the references of the retrieved articles. Fixed- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 37 publications
0
22
1
2
Order By: Relevance
“…26 On the contrary, our results showed that daily drinking of white spirits was a risk factor for kidney stone formation. The differences might be attributed to the varied drinking habits of different races and countries.…”
Section: Discussioncontrasting
confidence: 54%
“…26 On the contrary, our results showed that daily drinking of white spirits was a risk factor for kidney stone formation. The differences might be attributed to the varied drinking habits of different races and countries.…”
Section: Discussioncontrasting
confidence: 54%
“…No author has reported a dedicated general approach in any country. This is in spite of good evidence that lifestyle and nutritional changes can indeed result in a reduction of urolithogenesis and thus the need for treatments [26,27] .…”
Section: Discussionmentioning
confidence: 97%
“…The concomitant finding of high urine pH (> 7.5) in few cases indicated that the patient might have formed an infection stone (magnesium ammonium phosphate + carbonate apatite). Low urine pH presents a risk for uric acid precipitation and subsequent stone formation [31].…”
Section: Discussionmentioning
confidence: 99%